THE ROLE OF COLOR IMAGE ISSUES IN TEACHING ELEMENTARY SCHOOL MATHEMATICS (Web of Teachers: Inderscience Research, 2024)
This article aims to develop the aesthetic taste and logical thinking of primary school students through the use of different colors in mathematics lessons, and to improve students' arithmetic calculation skills.